The potato mop-top virus TGB2 protein and viral RNA associate with chloroplasts and viral infection induces inclusions in the plastids - Cowan, Graham H.; Roberts, Alison G.; Chapman, Sean N.; Ziegler, Angelika; Savenkov, Eugene I.; Torrance, Lesley (Frontiers in Plant Science, 2012)
The potato mop-top virus (PMTV) triple gene block 2 (TGB2) movement protein fused to monomeric red fluorescent protein (mRFP-TGB2) was expressed under the control of the PMTV subgenomic promoter from a PMTV vector. The subcellular localisations and interactions of mRFP-TGB2 were investigated using confocal imaging (CLSM) and biochemical analysis. The results revealed associations with membranes of the endoplasmic reticulum, mobile granules, small round structures (1-2 µm in diameter) and chloroplasts. Expression of mRFP-TGB2 in epidermal cells enabled cell-to-cell movement of a TGB2 defective PMTV reporter clone, indicating that the mRFP-TGB2 fusion protein was functional and required for cell-to-cell movement. Protein-lipid interaction assays revealed an association between TGB2 and lipids present in chloroplasts, consistent with microscopical observations where the plastid envelope was labelled later in infection. To further investigate the association of PMTV infection with chloroplasts, ultrastructural studies of thin sections of PMTV-infected potato and Nicotiana benthamiana leaves by electron microscopy revealed abnormal chloroplasts with cytoplasmic inclusions and terminal projections. Viral coat protein, genomic RNA and fluorescently-labelled TGB2 were detected in plastid preparations isolated from the infected leaves, and viral RNA was localised to chloroplasts in infected tissues. The results reveal a novel association of TGB2 and vRNA with chloroplasts, and suggest viral replication is associated with chloroplast membranes, and that TGB2 plays a novel role in targeting the virus to chloroplasts.